Shadow war the untold story of jihad in Kashmir - Jamal, Arif (New Delhi Vij Books, 2009)
An account of the India-Pakistan conflict in the Kashmir region examines the hidden history behind the violence, including the training of insurgents by the Pakistani military, and how CIA money fell into the hands of Kashmiri jihadis.
Includes bibliographical references (p. [273]-303).
Keywords: Insurgency -- India -- Jammu and Kashmir; Insurgency -- Jammu and Kashmir (India)